2013
DOI: 10.1080/10919392.2013.837791
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Web and Mobile Interactivity on E-Retailers' Performance

Abstract: This study investigates the differential impact of machine and person interactivity in both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 100 publications
1
18
0
1
Order By: Relevance
“…The common concept of interactivity entails a sense of connection with users and making information available to them; interactivity has been considered a value vital to successful communication, marketing, advertising, web design, and mobile commerce (Cyr, Head, & Ivanov, 2009;Goggin & Spurgeon, 2007;Lee, 2005;Macias, 2003;Teo, Oh, & Liu, 2003). Previous researchers found that web interactivity and mobile interactivity affected e-retailers' operational performance (Gu, Oh, & Wang, 2013). Furthermore, interactivity has been shown to have both cognitive or utilitarian (e.g., Kim & Niehm, 2009;Sicilia, Ruiz, & Munuera, 2005) and affective or hedonic (e.g., Koufaris, 2002;Menon & Kahn, 2002;Yoo, Lee, & Park, 2010) effects.…”
Section: Relative Advantage: Interactivitymentioning
confidence: 97%
“…The common concept of interactivity entails a sense of connection with users and making information available to them; interactivity has been considered a value vital to successful communication, marketing, advertising, web design, and mobile commerce (Cyr, Head, & Ivanov, 2009;Goggin & Spurgeon, 2007;Lee, 2005;Macias, 2003;Teo, Oh, & Liu, 2003). Previous researchers found that web interactivity and mobile interactivity affected e-retailers' operational performance (Gu, Oh, & Wang, 2013). Furthermore, interactivity has been shown to have both cognitive or utilitarian (e.g., Kim & Niehm, 2009;Sicilia, Ruiz, & Munuera, 2005) and affective or hedonic (e.g., Koufaris, 2002;Menon & Kahn, 2002;Yoo, Lee, & Park, 2010) effects.…”
Section: Relative Advantage: Interactivitymentioning
confidence: 97%
“…He finds that all the elements but personalization increase customers' trust in mobile commerce, which in turn improves attitudes toward, and behavioral intentions to, engage in mobile commerce. Gu, Oh, and Wang (2013) discuss the natures and benefits of machine interactivity and person interactivity. Machine interactivity refers to interactions between humans and the medium.…”
Section: Experiences Of Using Interactive Features Of a Mobile Appmentioning
confidence: 99%
“…) Transaction at static environments (at home, office, etc.) Gu et al (2013) Further customization (the mobile is a personal tool) Less customization (the computer is a personal or corporate tool) Choi et al (2008) Access to a wider target Access to a more restricted target Liébana-Cabanillas et al (Davis et al, 1989;Rogers, 1995) and as a personal determinant when adopting m-commerce ( Jeong et al, 2009;San-Martín and López-Catalán, 2013). Previous research has shown that the propensity to use ICTs and, in general, the willingness to adopt new technologies are factors that have contributed to the development of m-commerce (Agrebi and Jallais, 2015;Bruner and Kumar, 2005;Thakur and Srivastava, 2013;Zhou, 2011).…”
mentioning
confidence: 99%
“…When shopping via mobile devices, differences in information between the buyer and the seller could be even more pronounced, since the buyer faces a series of disadvantages that would not occur in an offline environment, such as: failure to touch and test the product/service, distrust in payment and transmission of personal information through these devices, lack of experience in purchasing via this channel, lack of knowledge, unstable internet connections, among others (Gu et al, 2013;San-Martín, 2015). All of the above can transfer fear and a perception of opportunism to the customer in the context of m-commerce (Chemingui and Ben lallouna, 2013;Thakur and Srivastava, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation